Influence of neem cake on composting of food waste - Madasamy Arun Kumar; Madasamy Petchiammal; Ammaiyappan Selvam (The Bioscan, 2025)
This study aimed to evaluate the effect of neem cake as the additive with food waste (FW) and sawdust on improving the compost quality and composting. The food waste (FW), sawdust (SD) and neem cake (NC) was mixed at 1:1:0.2, w/w, dry basis (FW+SD+NC) while food waste + sawdust mix (FW+SD, 1:1 w/w dry basis) served as control. The mixtures were composted in 20-L bench scale composters for 42 days. The results revealed that addition of neem cake resulted in thermophilic peak temperature of 63oC while the thermophilic period prevailed for nearly three weeks which were significantly higher than the control. The nitrogen content of the FW+SD+NC treatment (2.20 %) was higher when compared with FW+SD treatment (1.94 %). The physicochemical properties of the FW+SD and FW+SD+NC composts were within the recommended compost standard range. Addition of 20% neem cake proved to be one of the most effective strategies for improving the composting process, enhancing compost quality, and reducing nitrogen loss during food waste composting.